Identification and characterization of class 1 integrons among multidrug-resistant uropathogenic Escherichia coli strains in Mexico. (January 2022) - González-Villalobos, Edgar; Ribas-Aparicio, Rosa María; Belmont-Monroy, Laura; Aparicio-Ozores, Gerardo; Manjarrez-Hernández, H. Ángel; Gavilanes-Parra, Sandra; Balcázar, José Luis; Molina-López, José
Abstract: This study aimed to identify and characterize integrons among multidrug-resistant (MDR) uropathogenic Escherichia coli (UPEC) from outpatients in Mexico City, Mexico. PCR assays were used to screen for the presence of class 1, 2 and 3 integrons, whose PCR products were sequenced to identify the inserted gene cassettes within the variable regions. Out of 83 tested strains, 53 (63.9%) were positive for the presence of class 1 integrons, whereas no integrons were detected in the remaining strains, regardless of their classes. Most of the strains carrying the intI1 gene belonged to the extraintestinal B2 (41.5%) and commensal A (32.1%) phylogroups, and to a lesser extent, the extraintestinal D (20.8%) and commensal B1 (5.7%) phylogroups. Moreover, 8 different gene cassette arrangements were detected, with dfrA17 and aadA 5 being the most common (32.1% of the class 1 integron-positive strains), which confer resistance to trimethoprim/sulfamethoxazole and aminoglycosides, respectively. Our results suggest that class 1 integrons are widely distributed among MDR-UPEC strains in Mexico, which may directly or indirectly contribute to the selection of MDR strains. These findings are important for a better understanding of the factors and mechanisms that promote multidrug resistance among UPEC strains. Highlights: Class 1 integrons were detected in 63.9% of the tested uropathogenic Escherichia coli (UPEC) strains. Class 1 integrons were mainly detected in pathogenic phylogroups B2 and D. Eight different gene cassette arrangements were detected, with dfrA17 and aadA5 being the most common.